Environmental reform in the information age : the contours of informational governance - Mol, A. P. J.; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
As the information revolution continues to accelerate, the environment remains high on public and political agendas around the world. These two topics are rarely connected, but information - its collection, processing, accessibility and verification - is crucial in dealing with environmental challenges such as climate change, unsustainable consumption, biodiversity conservation and waste management. The information society (encompassing entities such as the internet, satellites, interactive television and surveillance cameras) changes the conditions and resources which are involved in environmental governance: old modes and concepts are increasingly being replaced by new, informational ones. Arthur P. J. Mol explores how the information revolution is changing the way we deal with environmental issues; to what extent and where these transformations have (and have not) taken place; and what the consequences are for democracy and power relations. This book will appeal to scholars and students of environmental studies and politics, political sociology, geography and communications studies.
Introduction: new frontiers of environmental governance -- Part I. Theory -- From information society to information age -- Social theories of environmental reform -- Informational governance -- Part II. Praxis -- Monitoring, surveillance and empowerment -- Environmental state and information politics -- Greening the networked economy -- Environmental activism and advocacy -- Media monopolies, digital democracy, cultural clashes -- Information-poor environments: Asian tigers -- Part III. Conclusion -- Balancing informational perspectives.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Environmental policy; Environmental management; Information technology; Electronic books